Cultural openness, interpersonal justice, and job satisfaction among Millennials and seniors: evidence from Japanese target employees following M&A - Bebenroth, Ralf; Ismail, Maimunah (Research Institute for Economics and Business Administration, Kobe University, 2014)
This study compares the perceptions of Millennials with those of senior employees in a cross border acquisition. Literature on Millennials argues that since they are open-minded, it can be assumed they would enjoy greater job satisfaction after their firm is acquired by another company. We investigated how employees perceived interpersonal justice and its influence on job satisfaction, and to what extent employees’ culturally open mindedness mediated this relationship. The results showed that employees, regardless of age, enjoyed greater job satisfaction after an acquisition when they perceived that they were being treated fairly by the new management. This study also showed that senior employees, not the Millennials of the target firm were more culturally open-minded. However, culturally open minded seniors were the less job satisfied. Implications for human resource practices are discussed.